Dehydration of Ethanol on Zeolite based media using adsorption process - R. H. Abdeen, Fouad; Mel, Maizirwan; Al-Khatib, Ma'an Fahmi Rashid; Azmi, Azlin Suhaida (2011)
Fossil fuels diminution and the following increase in fuels price have directed researchers towards producing fuel ethanol from biological materials. The main challenge encountered in such production process is the removal of large excess amount of water within the produced ethanol. Distillation, though is an energy extensive process, is usually used to produce ethanol up to 95% purity. Production of higher purity ethanol is usually a major challenge due to the formation of an azeotrope. In this study, a small adsorber bed apparatus was constructed and used to purify ethanol up to 99.5%. The apparatus consists of fluid delivery system, adsorber bed subsystem, storage and sampling unit and adsorption column where adsorbents like zeolite can be packed. The apparatus is designed to be packed and repacked several times and with various types of adsorbents. 3A zeolites are used as adsorbent materials in this study. 3A zeolites proven to be efficient in removal of water from ethanolwater azeotrope since their pore size is less than 0.3nm which allows only water to adsorb to the inner large surface area of zeolite. An optimization process was performed for the dehydration process manipulating three process parameters, namely; feed concentration, feed flow rate and adsorption temperature. Optimum set was determined to be at 95 % feed concentration, 200 ml/min flow rate and 25 ºC adsorption temperature. Validation of the optimum set resulted in the production of ethanol of purity higher than 99.5% and with 91 % efficiency of recovery.